Gradual restoration of gait following unicompartmental knee arthroplasty: a prospective study - Ming Zhang; Haoyue Wang; Yu Zhang; Haochong Zhang; Quanlei Zhang; Xiaoran Zu; Wei Chai; Xiang Li (Journal of Orthopaedic Surgery and Research)
Abstract Background This study investigates the gait characteristics and clinical outcomes following Unicompartmental Knee Arthroplasty (UKA) to provide scientific evidence for optimizing postoperative rehabilitation and patient management. Methods Between December 2022 and November 2023, 34 patients with unilateral medial compartment knee osteoarthritis (KOA) underwent UKA. Preoperative and postoperative videos of patients in standing, walking (side view), squatting, and supine knee-bending positions were captured using smartphones. Gait parameters including gait cycle, swing time, swing phase, stance time, stance phase, double support time, walking speed, step time, cadence, step length, stride length, stride width, active knee flexion angle, and maximum hip and knee flexion angles during squatting were analyzed using the MediaPipe framework for human pose estimation. Results Postoperative WOMAC scores were significantly lower than preoperative scores (P < 0.001), while postoperative KSS scores were significantly higher than preoperative scores (P < 0.001).Compared to preoperatively, postoperative affected-side gait speed, step length, step width, and active knee flexion angle all increased (P < 0.05). Additionally, postoperative gait cycle time and double-limb support time were reduced compared to preoperative values (P < 0.05). Among the 17 patients who could perform squats preoperatively and postoperatively, the maximum knee flexion angle and hip flexion angle in the squat position increased from preoperative values of (96.41 ± 20.65)° and (113.77 ± 22.56)° to postoperative values of (110.15 ± 20.79)° and (124.84 ± 21.13)°. Conclusions UKA significantly enhances knee joint kinematics, facilitating the transition from basic to advanced functional activities.